Efek Menulis Ekspresif terhadap Kualitas Hidup pada Pasien Kanker - Alvian Harisandy; Allenidekania Allenidekania; Giur Hargiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to evaluate the effect of expressive writing on quality of life in cancer patients. Data search methods were through the SpringerLink, Embase, PubMed, Proquest, and Scopus databases; all searches were carried out with complete articles with abstracts, quantitative research, both RCTs and other designs, and a selection of English language articles from 2017 to 2022, all articles were analyzed using assessment quality using JBI tools. The research results showed that 716 participants from 7 studies were analyzed in this systematic review; seven studies used an RCT design, five studies showed that expressive writing significantly improved the quality of life of cancer patients, and two studies were insignificant. In conclusion, explicit writing intervention is feasible and safe as a simple, accessible, inexpensive exercise. It has positive results related to improving the quality of life of cancer patients. Keywords: Expressive Writing, Cancer Patients, Improved Quality of Life